Integrative profiling of lung cancer biomarkers EGFR, ALK, KRAS, and PD-1 with emphasis on nanomaterials-assisted immunomodulation and targeted therapy - Peng, Li; Li, Hongmei; Yan, Wencai; Liu, Yingjie; Zhu, Haihao; Hong, Yingcai (Frontiers in Immunology, 2025)
BackgroundLung cancer remains the leading cause of cancer-related mortality globally, primarily due to late-stage diagnosis, molecular heterogeneity, and therapy resistance. Key biomarkers such as EGFR, ALK, KRAS, and PD-1 have revolutionized precision oncology; however, comprehensive structural and clinical validation of these targets is crucial to enhance therapeutic efficacy.MethodsProtein sequences for EGFR, ALK, KRAS, and PD-1 were retrieved from UniProt and modeled using SWISS-MODEL to generate high-confidence 3D structures. Protein–protein interaction (PPI) networks were constructed via STRING to explore functional associations and signaling networks. Molecular docking using SwissDock evaluated the binding affinities of established inhibitors. Transcriptomic validation was conducted using RNA-seq datasets from GEPIA2, TNMplot, and UALCAN to assess differential expression and clinical subgroup relevance. Experimental validation was performed via qRT-PCR in NSCLC cell lines (A549, H1975, H520).ResultsRobust 3D models were obtained, with MolProbity scores between 0.67 and 2.09, confirming structural reliability. Key mutations, including EGFR T790M and KRAS G12C, were localized to ATP-binding clefts and allosteric pockets respectively, based on structural mapping using SWISS-MODEL. PPI analysis revealed EGFR’s integration into ERBB and MAPK/PI3K pathways, ALK’s fusion-driven activation via EML4 and PI3K-AKT signaling, KRAS’s links to MAPK effectors, and PD-1’s interaction with immune checkpoint ligands PD-L1/PD-L2. Docking results showed strong EGFR–Gefitinib affinity (−5.94 kcal/mol, Kd 4.38 × 10-5 M), while KRAS inhibitors Adagrasib and Sotorasib demonstrated moderate binding (−3.94 and −3.72 kcal/mol, respectively). Transcriptomic analyses revealed significant overexpression of EGFR (2.8-fold), KRAS (2.3-fold), ALK (1.9-fold), and PDCD1 (2.1-fold) in NSCLC tissues (p < 0.01). qRT-PCR corroborated these findings, with H1975 cells displaying elevated EGFR (3.2-fold) and KRAS (2.4-fold), and H520 cells showing increased ALK (2.7-fold) and moderate PDCD1 expression.ConclusionThis integrative study combining structural modeling, molecular interaction analysis, and transcriptomic validation confirms EGFR, ALK, KRAS, and PD-1 supports their relevance as clinically actionable and structurally druggable biomarkers in NSCLC. These findings support their continued use in targeted therapy design and precision diagnostics, highlighting nanomaterials as ideal carriers due to their ability to enhance immune checkpoint blockade and drug bioavailability in NSCLC.